Kepadatan Populasi dan Pola Penyebaran Lalat Buah (Bactrocera Spp.) (Diptera : Tephritidae) yang Menyerang Buah Mangga (Mangifera Indica L.) di Kabupaten Buleleng - KOMANG BADRIASIH; I WAYAN SUPARTHA; I WAYAN SUSILA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Population Density and Distribution Patterns Fruit Flies (Bactrocera spp.) (Diptera: Tephritidae) that Attacking Mangoes (Mangifera indica L.) in Buleleng Regency The research population density and distribution patterns fruit flies (Bactrocera spp.) that attacking mangoes (Mangifera indica L.) in Buleleng Regency was conducted to determine diversity, population density, similarity index type and distribution patterns of population of fruit flies attacking mangoes. The study was conducted since October 2018 up to March 2019 by using purposive method to take mangoes attacked by fruit flies in Buleleng Regency. The results showed that three were species of fruit flies that attacked mangoes in Buleleng Regency, that are B. papayae, B. carambolae and B. occipitalis. Population density of B. papayae was higher than density population of B. carambolae and B. occipitalis. Average population density of B. papayae, B. carambolae and B. occipitalis were 9,36 adult/fruit, 5.15 adult/fruit and 0,04 adult/fruit, respectively. Type similarity index has a range of values from 80 – 100% with population distribution randomly (S2/X = 1) at each study location.